The New Institutionalism in Organizational AnalysisThe New Institutionalism in Organizational Analysis, edited by PowellWalter W. and DiMaggioPaul J. Chicago: University of Chicago Press, 1991, 478 pp., $24.95, paper. - Romanelli, Elaine (Academy of Management Review, 1992)
This article presents a review of the book ?The New Institutionalism in Organizational Analysis,? edited by Walter W. Powell and Paul J. DiMaggio.